2,3-Diaminopyridinium benzoate - Balasubramani, Kasthuri (International Union of Crystallography, 2009)
In the title compound, C(5)H(8)N(3) (+)·C(7)H(5)O(2) (−), the pyridine N atom is protonated. The carboxylate group of the benzoate anion is twisted away from the attached ring by 10.91 (9)°. In the crystal structure, N—H⋯O hydrogen bonds between 2,3-diaminopyridinium cations and benzoate anions, and π–π interactions between the pyridinium rings [centroid–centroid distance = 3.6467 (9) Å] form a two-dimensional network parallel to (001). In the network, N—H⋯O hydrogen bonds form R (2) (2)(8) and R (2) (1)(7) ring motifs.